POST 2012 CLIMATE CHANGE AGREEMENT - Malvina Tema; Magda Suchon; Christa Biervliet; Nika Jeiranashvili; Peter Pie, Rachminawati (European Scientific Journal, ESJ, 2014)
Addressing climate change requires a thorough and sincere communication not only as to the scale of the challenge the world faces but also as to the international cooperation possibilities and countries willingness to commit to the challenge. Taking the lead in this group, European Union has acknowledged the fact that climate change is a serious social, political and economic challenge. Following the indications provided by the scientific rationale as to the urgent action that is required, European Community has involved itself in fight against the phenomena by engaging in working on a feasible solution to this problem. European Commission in particular has been taking upon its shoulders much of the workload in this field and has proved its dedication especially by involving stakeholders in constant dialogue on the subject. Sharing the ambitions of the European Commission in creating a cleaner world, the major goal of this paper is to provide the Commission with a series of recommendations from a development/political, environmental and economic perspective to ensure that the ambitions become a reality, and therefore a success. Accordingly, this paper provides an overview of sectoral and general approaches' effectiveness in terms of their economic and environmental as well as compliance prospects. Conclusion wraps up the paper providing a number of recommendations stemming mainly from stakeholders input's analysis.